Impaired glucocorticoid-mediated HPA axis negative feedback induced by juvenile social isolation in male rats. (1st May 2018) - Boero, Giorgia; Pisu, Maria Giuseppina; Biggio, Francesca; Muredda, Laura; Carta, Gianfranca; Banni, Sebastiano; Paci, Elena; Follesa, Paolo; Concas, Alessandra; Porcu, Patrizia; Serra, Mariangela
Abstract: We previously demonstrated that socially isolated rats at weaning showed a significant decrease in corticosterone and adrenocorticotropic hormone (ACTH) levels, associated with an enhanced response to acute stressful stimuli. Here we shown that social isolation decreased levels of total corticosterone and of its carrier corticosteroid-binding globulin, but did not influence the availability of the free active fraction of corticosterone, both under basal conditions and after acute stress exposure. Under basal conditions, social isolation increased the abundance of glucocorticoid receptors, while it decreased that of mineralocorticoid receptors. After acute stress exposure, socially isolated rats showed long-lasting corticosterone, ACTH and corticotrophin releasing hormone responses. Moreover, while in the hippocampus and hypothalamus of group-housed rats glucocorticoid receptors expression increased with time and reached a peak when corticosterone levels returned to basal values, in socially isolated rats expression of glucocorticoid receptors did not change. Finally, social isolation also affected the hypothalamic endocannabinoid system: compared to group-housed rats, basal levels of anandamide and cannabinoid receptor type 1 were increased, while basal levels of 2-arachidonoylglycerol were decreased in socially isolated rats and did not change after acute stress exposure. The present results show that social isolation in male rats alters basal HPA axis activity and impairs glucocorticoid-mediated negative feedback after acute stress. Given that social isolation is considered an animal model of several neuropsychiatric disorders, such as generalized anxiety disorder, depression, post-traumatic stress disorder and schizophrenia, these data could contribute to better understand the alterations in HPA axis activity observed in these disorders. Highlights: Social isolation (SI) induced long-lasting CRH, ACTH and CORT responses after acute stress. SI impairs MR and GR balance in the hippocampus and hypothalamus. SI alters GR expression and function. SI alters the hypothalamic endocannabinoid system.